Floristic Composition and Ecological Characteristics of Shahbaz Garhi, District Mardan, Pakistan (Global Journal of Science Frontier Research, 2014)
The study was designed to explore the floristic composition and biological characteristics of the area. A record of plant species of Shahbaz Garhi, Mardan was organized during 2009 -2010. A record of plant species was organized on the source of field trips conducted in winter, summer and monsoon and identified with available literature. The plants were classified into different life form and leaf size classes after standard methods. The flora consisted of 132 plant species belonging to 104 genera and 47 families. Asteraceae and Poaceae are the dominant families. The biological spectrum explains that therophytes (63 spp., 47.73%) were the dominant followed by chamaephytes (24 spp., 18.18%), magaphanerophytes (15 spp., 11.36%), hemicryptophytes (13 spp., 9.85%), nanophanerophytes (12 spp., 9.09%), geophytes (4 spp., 3.03%) and parasite (1 spp., 0.76%). Leaf size classes of plants consisted of microphylls (62 spp., 46.97%), mesophylls (28 spp., 21.21%), nanophylls (18 spp., 13.64%), leptophylls (15 spp., 11.36%) and megaphylls (9 spp., 6.82%). Analysis of the study reveals the phytoclimate to be of therophytic type. The domination of therophytes indicates that the investigated area is under deep biotic stress.
Keywords: flora; ecological characteristics; shahbaz garhi; mardan; pakistan